2020
DOI: 10.1680/jstbu.18.00042
|View full text |Cite
|
Sign up to set email alerts
|

Performance of concrete containing recycled springs in post-fire conditions

Abstract: The main objective of this study was to assess the performance of concrete containing recycled springs with various volume fractions of 0·2, 0·4 and 0·6% at temperatures of 25, 100, 250, 500, 700 and 900°C. In addition, a comparison between concrete mixes containing steel and polypropylene fibres was performed using tensile and compressive strength tests to attain an optimum mix design. The results showed that the compressive and tensile strengths of concrete specimens were improved by adding the percentages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Six target temperatures ( T u ) of 25, 100, 250,500,700, and 900°C were selected. The target temperatures were selected according to the behavior of concrete in different conditions which have been investigated in previous studies 23,24 . After reaching the target temperature, temperature will be constant for 60 min until the sample reaches thermal stability stage and uniform distribution of heat is achieved.…”
Section: Test Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six target temperatures ( T u ) of 25, 100, 250,500,700, and 900°C were selected. The target temperatures were selected according to the behavior of concrete in different conditions which have been investigated in previous studies 23,24 . After reaching the target temperature, temperature will be constant for 60 min until the sample reaches thermal stability stage and uniform distribution of heat is achieved.…”
Section: Test Methodsmentioning
confidence: 99%
“…The study of concrete delamination and its mechanical properties are the most important focuses of this research. Pachideh et al 23,24 investigated the performance of concrete containing recycled springs, steel, and polypropylene fibers at different temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous research, the volume fraction of 0.4% was considered as an optimum and suitable mix design for fibers and springs 24 . Note that using more than 0.6% of metal springs may cause the increasing possibility of their intertwist 25 …”
Section: Experimental Programmentioning
confidence: 99%
“…The high temperatures led to evaporating the water inside the concrete. This matter contributed to the porosity or so‐called crystallization of the concrete 25 …”
Section: Experimental Programmentioning
confidence: 99%
“…It was observed that the presence of the spring decreases cracks’ depth and width. It was found that incorporation of 0.2% spring, is regarded as the optimum ratio (Pachideh et al, 2020). In 2019, Pachideh and Gholhaki attempted to evaluate the effect of steel and polypropylene fibers as well as metal springs on the post-heat behavior of ordinary concretes.…”
Section: Introductionmentioning
confidence: 99%